Tobacco farming in rural Vietnam: questionable economic gain but evident health risks - Bich Nguyen; Giang Kim; Van Minh Hoang; Huong Nguyen (BMC, 2009)
Abstract Background In order to provide evidence on health impacts of the tobacco industry on cultivators in Vietnam, this study aims to provide comparison between tobacco cultivation related revenue and expenditure in selected areas in rural Vietnam and examine the relationship between tobacco cultivation and self-reported illness in the study population. Methods Two tobacco farming communes and two non-tobacco farming communes were selected for this study. In each selected commune, 120 households were sampled using two-stage cluster sampling technique. Local health workers were recruited and trained to conduct household interviews using structured questionnaire. Results Where the expenditure figures do not include personnel costs (as the farming work was almost always responsible by the family members themselves), it appeared that the average tobacco farmer did benefit financially from tobacco cultivation. However, if a personal opportunity cost was added to give a financial value to their labour, the profit from tobacco cultivation was seen to be minimal. The occurrences of 9 out of the 16 health problems were statistically significant higher among tobacco growing farmers compared to that among non-tobacco farmers. Tobacco farming was shown to be the second strong predictor of self-reported health problems among the farmer (after the effect of old age). Conclusion The present study provides evidence that can be used to increase public awareness about the harmful effects of tobacco growing.